2018
DOI: 10.1177/1528083718772299
|View full text |Cite
|
Sign up to set email alerts
|

Through-the-thickness reinforcement for composite structures: A review

Abstract: Three-dimensional preforms have been developed in order to remedy and minimize the out-of-plane damage caused by 2D structures. Several researches have been done on more complex structures which have more interesting mechanical characteristics through-the-thickness. A wide spectrum of 3D textile technologies encompassing weaving, knitting, stitching, z-pinning, tufting, etc. is used to manufacture through-the-thickness reinforced materials. This kind of reinforcement aims to achieve a balance between the in-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…Fibers 2020, 8, 15 2 of 14composites. These works showed that the architecture of the reinforcement has a preponderant role on the mechanical properties of the composite.Generally, 3D architectures can be obtained by combining multi-layers of stacked 2D fabric with a through-the-thickness fiber reinforcement, introduced using stitching, z-pining, or tufting technologies [10][11][12]. Another technology is the 3D warp interlock weaving, in which multi-layers of in-plane yarns are bound together by a group of binding warp yarns according to a specific architecture (light blue in Figure 1) [13].…”
mentioning
confidence: 99%
“…Fibers 2020, 8, 15 2 of 14composites. These works showed that the architecture of the reinforcement has a preponderant role on the mechanical properties of the composite.Generally, 3D architectures can be obtained by combining multi-layers of stacked 2D fabric with a through-the-thickness fiber reinforcement, introduced using stitching, z-pining, or tufting technologies [10][11][12]. Another technology is the 3D warp interlock weaving, in which multi-layers of in-plane yarns are bound together by a group of binding warp yarns according to a specific architecture (light blue in Figure 1) [13].…”
mentioning
confidence: 99%
“…Although carbon fiber reinforced polymers have been reported to possess good mechanical properties in the warp and filling direction, it is through-the-thickness, direction had suffered low intralaminar properties as a form of splitting or intraand inter-laminar delamination. [15,16] To improve the out-of-plane properties of the TSC, z-fiber was basically introduced to two dimensional (2D) biaxial textile fabric by using stitching, [17] three dimensional (3D) weaving, [18][19][20] 3D braiding, [21] and 3D nonwoven techniques. [16] Recently, single or multiwall carbon nanotubes (SWCNTs or MWCNTs) were developed by using various techniques such as arc discharge, [22][23][24][25] laser ablation, [26][27][28] or chemical vapor deposition (CVD).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many proposed solutions for increasing the fracture toughness of laminated composites, and two of the most common methods include stitching [1][2][3] and z-pinning. 3,4 In both of these methods, the composite preform is first compiled, and the through-thickness reinforcement is later inserted into the preform. These reinforcements are also typically inserted orthogonal to the fibers in the laminate, purely in the 3-direction respective to the fibers.…”
Section: Introductionmentioning
confidence: 99%